PRINSIP KERJA SAMA PRINSIP KERJA SAMA DALAM TUTURAN GURU DI SMAN 3 GUNUNG SAHILAN KABUPATEN KAMPAR - Hesty Elfianora Hesty; Fatmawati (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
This research is motivated by the gap between Grice's theory and the culture of Indonesian society. Differences between western culture and Indonesian culture give rise to utterances that contain maxims in the principle of cooperation. Discusses issues regarding compliance with and violations of cooperative principles, and reasons for violations of work principles. This study aims to describe the cooperative principle contained in the teacher's utterances, both those who obey and those who violate. This research is guided by the theory put forward by Grice about the principle of cooperation. The approach in this study is a qualitative approach with content analysis methods. The data in this study are all teacher conversations that contain the principle of cooperation. The source of the data in this study was teacher conversations at SMAN 3 Gunung Sahilan, Kampar Regency, Riau. The techniques used in data collection are observation techniques, note-taking techniques, and interview techniques. The results of the study suggest that of the four maxims, the dominant maxims that appear are the maxims that obey, because these utterances are taken from the utterances of teachers in the school environment. The school environment is a formal environment. So that it raises more adherence to maxims in the utterances that occur. However, even though school is a formal environment, the teacher's speech does not always fulfill the principle of cooperation, sometimes when speaking the teacher can violate the principle of cooperation. This is due to several reasons, such as; familiarity, want to create humor, want to explain something in detail, want to be polite, and want to look polite.